2018
DOI: 10.1371/journal.pntd.0006786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, infection prevalence, and possible transmission routes of Bartonella spp. in vampire bats

Abstract: Bartonella spp. are globally distributed bacteria that cause endocarditis in humans and domestic animals. Recent work has suggested bats as zoonotic reservoirs of some human Bartonella infections; however, the ecological and spatiotemporal patterns of infection in bats remain largely unknown. Here we studied the genetic diversity, prevalence of infection across seasons and years, individual risk factors, and possible transmission routes of Bartonella in populations of common vampire bats (Desmodus rotundus) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 77 publications
4
56
0
Order By: Relevance
“…are genetically diverse and geographically widespread in Brazil. Herein, many different Bartonella genotypes were detected in D. rotundus , as similarly reported by previous studies conducted in Latin America (Becker, Bergner, et al, ). Bai et al () detected 7 gltA Bartonella genetic variants among D. rotundus sampled in Guatemala, whereas (Becker, Bergner, et al, ; Becker, Czirják, et al, ) reported 11 genotypes in common vampire bats sampled in Peru and Belize.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…are genetically diverse and geographically widespread in Brazil. Herein, many different Bartonella genotypes were detected in D. rotundus , as similarly reported by previous studies conducted in Latin America (Becker, Bergner, et al, ). Bai et al () detected 7 gltA Bartonella genetic variants among D. rotundus sampled in Guatemala, whereas (Becker, Bergner, et al, ; Becker, Czirják, et al, ) reported 11 genotypes in common vampire bats sampled in Peru and Belize.…”
Section: Discussionsupporting
confidence: 87%
“…Herein, many different Bartonella genotypes were detected in D. rotundus , as similarly reported by previous studies conducted in Latin America (Becker, Bergner, et al, ). Bai et al () detected 7 gltA Bartonella genetic variants among D. rotundus sampled in Guatemala, whereas (Becker, Bergner, et al, ; Becker, Czirják, et al, ) reported 11 genotypes in common vampire bats sampled in Peru and Belize. While gltA Bartonella genotypes detected in Brazilian vampire bats grouped in six different clusters, highlighting a high genetic diversity, rpoB genotypes detected in the present study grouped more tightly, albeit showing some subclustering.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Vampire bats, in particular, are widely distributed from northern Mexico to northern Argentina and, owing to their blood-feeding diet, can transmit pathogens such as rabies virus. Feeding on vertebrate blood may also facilitate cross-species transmission of other pathogens such as Bartonella, hemoplasmas, influenza, and trypanosomes (Becker, Bergner, et al, 2018a;Hoare, 1965;Tong et al, 2013;Volokhov et al, 2017). Feeding on vertebrate blood may also facilitate cross-species transmission of other pathogens such as Bartonella, hemoplasmas, influenza, and trypanosomes (Becker, Bergner, et al, 2018a;Hoare, 1965;Tong et al, 2013;Volokhov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%